Anti-complement Treatment for Paroxysmal Nocturnal Hemoglobinuria: Time for Proximal Complement Inhibition? A Position Paper From the SAAWP of the EBMT - Risitano, Antonio M.; Marotta, Serena; Ricci, Patrizia; Marano, Luana; Frieri, Camilla; Cacace, Fabiana; Sica, Michela; Kulasekararaj, Austin; Calado, Rodrigo T.; Scheinberg, Phillip; Notaro, Rosario; Peffault de Latour, Regis (Frontiers in Immunology, 2019)
The treatment of paroxysmal nocturnal hemoglobinuria has been revolutionized by the introduction of the anti-C5 agent eculizumab; however, eculizumab is not the cure for PNH, and room for improvement remains. Indeed, the hematological benefit during eculizumab treatment for PNH is very heterogeneous among patients, and different response categories can be identified. Complete normalization of hemoglobin (complete hematological response), is seen in no more than one third of patients, while the remaining continue to experience some degree of anemia (major and partial hematological responses), in some cases requiring regular red blood cell transfusions (minor hematological response). Different factors contribute to residual anemia during eculizumab treatment: underlying bone marrow dysfunction, residual intravascular hemolysis and the emergence of C3-mediated extravascular hemolysis. These two latter pathogenic mechanisms are the target of novel strategies of anti-complement treatments, which can be split into terminal and proximal complement inhibitors. Many novel terminal complement inhibitors are now in clinical development: they all target C5 (as eculizumab), potentially paralleling the efficacy and safety profile of eculizumab. Possible advantages over eculizumab are long-lasting activity and subcutaneous self-administration. However, novel anti-C5 agents do not improve hematological response to eculizumab, even if some seem associated with a lower risk of breakthrough hemolysis caused by pharmacokinetic reasons (it remains unclear whether more effective inhibition of C5 is possible and clinically beneficial). Indeed, proximal inhibitors are designed to interfere with early phases of complement-activation, eventually preventing C3-mediated extravascular hemolysis in addition to intravascular hemolysis. At the moment there are three strategies of proximal complement inhibition: anti-C3 agents, anti-factor D agents and anti-factor B agents. These agents are available either subcutaneously or orally, and have been investigated in monotherapy or in association with eculizumab in PNH patients. Preliminary data clearly demonstrate that proximal complement inhibition is pharmacologically feasible, apparently safe, and may drastically improve the hematological response to complement inhibition in PNH. Indeed, we envision a new scenario of therapeutic complement inhibition, where proximal inhibitors (either anti-C3, anti-FD or anti-FB) may prove effective for the treatment of PNH, either in monotherapy or in combination with anti-C5 agents, eventually leading to drastic improvement of hematological response.